Project compatibility with the aid of BIM: analysis of cost reduction in a social housing project (Research, Society and Development, 2022)
BIM technology has helped the development of civil construction in several ways. One of them is through the improvement of management of building projects. In this sense, this article aims to present an analysis on the reduction of construction costs, allowed through project management using BIM, taking as basis a project developed for a housing complex for the city of Timbaúba, Pernambuco. Given the above, this work is characterized as a case study, since it describes and analyzes the work of a company, BIM user and project manager, in reducing the costs of the above mentioned work. As results, it was possible to note, among other factors, that the management with the aid of the tool collaborated to reduce the amount of construction material and, consequently, the cost of each house. The conclusion shows that BIM contributes significantly to project management, enabling, for example, high savings in construction costs, especially when considering the magnitude of housing projects.